A study on the efficacy of guava decoction in reducing gingival margin inflammation - Aquino, Claire Anne L.; Campos, Isabel G.; de Castro, Elizabeth (Adviser).
A study consisting of two phases (oral examination before rinsing and recording of scores after rinsing) was conducted in order to determine if guava decoction is effective in reducing gingival margin inflammation. Thirty subjects were utilized in the study and they consisted of male and female grade four school children from the University of the Philippines Integrated School in Diliman, Quezon City. The subjects were divided into two study groups namely, Group A and Group B, wherein Group A served as the experimental group and Group B as the control group. The subjects were examined for gingivitis and plaque scores, and these were recorded prior to rinsing of the mouthwashes after every meal for seven days. The subjects were then recalled after seven days and scores were recorded again. If we are to draw the conclusions of the herein scientific procedure undertaken, we would conclude that there is no sufficient evidence to claim that guava decoction is effective in reducing gingival margin inflammation.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gingivitis; Herbs -- Therapeutic use; Guava -- Therapeutic use